Artefatti, reperti e mondo di natura. Realismo e teoria dei simulacri in Philip K. Dick - Cuozzo, Gianluca (Itinerari, 2024)
Starting from the 1950s, Philip Dick, while dissimulating his criticism of the mainstream genre, analyzed American society with a perspective that was ahead of its time as well as being alienating. In the midst of the post-war economic boom, he obsessively searched for cracks in that opulent society which had caused the severe degradation of the landscape and the profound alienation of inter-human relationships. This alienation was produced by the technological progress and by its strategies, which were aimed at the (non-negotiable) achievement of material well-being. The theme of waste, analyzed with an aim that is both critical and theological, eventually became a true leitmotif of Dick’s literary production. The aim of the present paper is to analyze the philosophical significance of terms such as kipple and gubble, and to identify their metaphysical facets.